(untitled) (Dhaka University Journal of Science, 2019)
Overweight or obesity has adverse effects on health as the risk of diabetes and cardiovascular disease is very high among overweight or obese women. Even mortality rate among overweight and obese people is more than that of normal or underweight people. The risk of facing adverse maternal and fetal complications during pregnancy, delivery, and postpartum is higher among overweight/obese women. In Bangladesh, the percentage of overweight/obesity among ever married women which was only 9 percent in 2004 was found to be 24 percent in 2014. The main purpose of the study is to determine the responsible factors for the overweight or obesity among ever married women aged 15-49 years in Bangladesh. Data have been taken out from Bangladesh Demographic and Health Survey (BDHS), 2014 to serve this purpose. Since there are 600 clusters in BDHS data, cluster effects are taken into account to find the estimates of the regression parameters by applying mixed logistic regression model. The results obtained from the model show that women from poor family (OR = 0.69), living in Rangpur (OR=0.83) and Sylhet regions (OR = 0.66), currently working (OR = 0.79) and using modern contraceptive (OR = 0.88) are significantly less overweight/obese than women from middle class family, living in Dhaka region, currently not working and using contraceptive except modern type, respectively. On the other hand, women from urban residence (OR = 1.54), having education and educated husband, women from rich family (OR = 1.63), married women (OR = 1.48), older age, watching TV at least once in a week (OR = 1.35) and having two or three ever born children (OR = 1.31) are more overweight/obese than their respective counterpart. Dhaka Univ. J. Sci. 67(2): 85-90, 2019 (July)